Impact evaluation of SLM options to achieve land degradation neutrality: ICARDA-iMMAP report. - Jaspe, Jim (2017)
API development for SLM Form integration, WebGIS UI enhancement, load remaining datasets, added functionality to show context socio-ecological type(s) CSET, application and maps optimization.